Efficacy of intramuscular injections of biotin and dexpanthenol in the treatment of diffuse hair loss: A randomized, double‐blind controlled study comparing two brands. Issue 9 (15th July 2022) - Samadi, Aniseh; Ketabi, Yasaman; Firooz, Rojin; Firooz, Alireza
Abstract: Combination therapy with biotin and dexpanthenol is a well‐known practice in preventing and treating hair loss, however, it is not well studied. In this study, we compared the efficacy of the 6‐week treatment with two brands of biotin and dexpanthenol for the treatment of diffuse hair loss. Fifty eligible patients with diffused pattern hair loss, (41 women and 9 men) were randomized in a 1:1 ratio to receive either 6 weekly injections of dexpanthenol ampoule 250 mg/2 ml and biotin ampoule 5 mg/1 ml, manufactured by Pars Behvarzan or Bayer Company. Combing test, Standard scalp photography and trichoscan assessment were performed before the first treatment session and one and 8 weeks after the last one. Patients' satisfaction and drug adverse reactions were also recorded. One and eight weeks after the last treatment session, hair fall count and total hair density significantly improved in both groups ( p ‐value <0.01 for hair fall count and 0.04 and 0.02, for hair density in Pars and Bayer groups, respectively). There was no significant difference between the two groups in any other trichoscan parameter, except for improvement in terminal/vellus hair ratio in the Bayer group in both follow up visits, compared to the Pars group ( p ‐value = 0.02 and 0.033 for weeks one and eight). Six‐week treatment with both brands of biotin and dexpanthenol was effective and safe in people with diffused pattern hair loss.